Optimalisasi Pemberdayaan Kemaslahatan Ekonomi Masyarakat Desa Melalui Badan Usaha Milik Desa (BUMDes) (Studi Penelitian Terhadap UMKM Keripik Singkong di Desa Nanggerang, Kecamatan Tajurhalang, Kabupaten Bogor) - Awang Darmawan Putra; Rina Desiana (Maqrizi: Journal of Economics and Islamic Economics, 2021)
In facing the current global economic era, the government should pay special attention, especially to empowering superior Human Resources (HR). The presence of BUMDes in the form of micro, small, and medium enterprises are a medium for the community to develop their economy, and every muamalah that is carried out should be in accordance with the purpose of benefit, namely the benefit of the community's economy. This study analyzes the optimization of the empowerment of the economic benefits of rural communities through BUMDes. The methodology of this research is qualitative with a descriptive approach. This research design uses primary and secondary data. The results showed that the aspects of Hifz al-Din, Hifz al-Nasl, and Hifz al-Mal had been achieved. The aspect of Hifz al-Nafz has not been achieved and while Hifz al-'Aql has not been fully fulfilled. The advice obtained from the results of the research to the Nanggerang Village apparatus is to be able to build awareness of the community about the importance of an education even though it is non-formal education, such as training in entrepreneurial development, because by increasing the knowledge of creativity in entrepreneurship, it is universally possible to improve the community's economy much better.